The evaluation of anti-tuberculosis activities in public health routine - Arantes, Gilberto Ribeiro (Revista de Saúde Pública, 1974)
The evaluation of the anti-tuberculosis services delivered to a population may be achieved in function of the effectiveness reached by periodically measuring the prevalence of infection in an age group selected for this purpose. The evaluation of the activities concerning to the efficiency or even to the efficacy may be commonly processed in function of the discovering and treatment of cases, vaccination, chemoprophylaxis and focus control. The feasibility of the process will depend on the existence of reports containing the necessary informations.